Efektivitas Pijat Marmet terhadap Pengeluaran ASI pada Ibu Menyusui dengan Bendungan ASI - Maslan Pangaribuan; Farida Simanjuntak; Astuti Widia (PT Bukuloka Literasi Bangsa, 2026)
Breast engorgement during the postpartum period can impede milk removal and breastfeeding success. This study aimed to analyze changes in breast milk output after Marmet massage among breastfeeding mothers with breast engorgement. A pre-experimental study with a one-group pretest–posttest design involved 30 mothers selected through total sampling. Marmet massage was administered twice daily for approximately 15 minutes from postpartum day 3 to day 10. Breast milk output was measured before and after the intervention and analyzed using a paired t-test after the data were confirmed to be normally distributed. Mean breast milk output increased from 44.80 mL to 197.90 mL, with a mean difference of 153.10 mL. The analysis showed a significant difference (t = −51.057; p < 0.001). These findings indicate that Marmet massage was followed by increased breast milk output in the studied group. However, interpretation should consider the absence of a control group and other factors that may influence lactation. Keywords: breast engorgement, breast milk output, breastfeeding mothers, Marmet massage